Interaction of ibuprofen and probenecid with drug metabolizing enzyme phenotyping procedures using caffeine as the probe drug - Vrtic, Fatima; Haefeli, Walter E.; Drewe, Jürgen; Krähenbühl, Stephan; Wenk, Markus (British journal of clinical pharmacology, 2003)
Aims To examine the suspected inhibitory potential of the over-the-counter (OTC) drug ibuprofen on N-acetyltransferase 2 (NAT2) in vitro and in vivo and the possible implications for phenotyping procedures using caffeine as probe drug. Methods We first studied the inhibitory effect of ibuprofen on NAT2 in vitro, using human liver cytosol and sulfamethazine as substrate. In vivo 15 fast and 15 slow acetylating healthy volunteers were treated with a single dose of ibuprofen (800 mg) orally and phenotyped for NAT2, CYP1A2, and xanthine oxidase (XO) with caffeine as probe drug before and during drug treatment. Because of unexpected in vivo results with ibuprofen this study was repeated in 20 healthy volunteers with probenecid, a model substrate of renal organic anion transport (OAT). For phenotyping tests a urine sample was collected 6 h after caffeine (200 mg) intake. The caffeine metabolites acetyl-6-formylamino-3-methyluracil (AFMU), 1-methylxanthine (1MX), 1-methyluric acid (1MU), and 1,7-dimethyluric acid (17MU) were quantified by HPLC, and the corresponding metabolic ratios for CYP1A2, NAT2, and XO were then calculated. Genotyping for NAT2 was performed with standard PCR-RFLP methods. Results In vitro, with human liver cytosol an inhibition by ibuprofen of the acetylation of sulfamethazine with Ki values between 2.2 and 3.1 mm was observed. Surprisingly, in vivo a significant (P < 0.001) increase of the acetyl-6-formylamino-3-methyluracil/1-methylxanthine (AFMU/1MX) urinary ratio from 0.97 ± 0.16 to 1.08 ± 0.18 (95% CI on the difference 0.049, 0.170) was found, indicating an apparent elevation of NAT2 activity. In contrast, no change was observed for the ratios used for XO and CYP1A2. Because an induction of NAT2 could be excluded, an interaction of ibuprofen with the tubular secretion of some of the caffeine metabolites was assumed. To prove this assumption, the in vivo study was repeated with probenecid, a model substrate of the renal OAT system. Again, a prominent elevation of the AFMU/1MX ratio from 0.97 ± 0.21 to 1.53 ± 0.35 was found (P < 0.002; 95% CI on the difference 0.237, 0.876), but also the XO ratio 1MU/1MX was significantly (P < 0.0001) increased from 1.34 ± 0.09 to 2.24 ± 0.14 (95% CI on difference 0.735, 1.059) due to a reduction of 1MX excretion. Conclusions Substrates of OAT interact with renal excretion of caffeine metabolites and may falsify NAT2 and XO phenotyping results. Other phenotyping procedures, which are based on urinary metabolic ratios, should also be validated in this respect, especially in patients under polymedication.